The Role of The Traditional Beliefs of the Toba Batak Community in Social Practices in the Lake Toba Region: A Review of Culture and Context - Firmando, Harisan Boni (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This article aims to see the extent of the traditional beliefs of the Toba Batak people and their relevance in people's lives in the Lake Toba area. This research uses qualitative methods with data collection techniques of observation, interviews, document studies and focus group discussions (FGD). The results of the research show that the Batak belief in Mulajadi Na Bolon (the great Creator) is synthetic, which is reflected in a belief in the totality of various different elements, which encompasses three continents. The three banua are ruled by three gods who in their unity maintain order in the cosmos, the totality of the three is called Debata na tolu (three Gods), sitolu Suhut, Sitolu Harajaon (three hosts, three kingdoms). The belief in totality is reflected in the existence of society, namely the totality of three functional elements called hula-hula, dongan sabutuha and boru. The alliance or totality of these three elements is called dalihan na tolu. The dalihan na tolu kinship system is magically religious so that it becomes the norm that allows society to live in harmony. The dalihan na tolu kinship system guides the behavior of people in the Lake Toba area in social activities, such as communicating, acting and resolving various social problems, especially in carrying out various traditional ceremonies. In traditional ceremonies, symbolic objects are exchanged which become a means of giving and receiving for the parties involved. The exchange of symbolic objects carried out is a meaningful symbol that has magical religious power so that people's lives can be harmonious and harmonious with nature and fellow humans.